LINEAR POLARIZATION OF RY TAURI AFTER ITS - Kardopolov, V. I.; Rspaev, F. K. (Одеські астрономічні публікації, 2017)
Simultaneous photoelectric and polarimetric BVR measurements of RY Tau have been obtained from 1987 December to 1993 March. A "flash" changed usual behavior of the star, possibly indicating the binarity of the system.